Analisa Performa Pembangkit Berdasarkan Tingkat Kevakuman Kondensor Pada PLTU Barru Unit 2 - Apollo Apollo; La Ode Musa; Amrul Ariyansyah G; Andi Aswarriansyah (Politeknik Negeri Ujung Pandang, 2015)
Vacuum condenser is one of the parameters that affect the performance of the plant. To keep the plant's performance remains stable then it takes a good degree of vacuum in the condenser. This final project aims to determine the performance of plants based on the level of vacuum condenser different. The method used is collecting data on the actual load conditions 50%, 75% and 100% and then perform data analysis. The results will be presented in tables and graphs then be deduced. Based on data and analysis that has been carried out, the results obtained are better condenser vacuum pressure, the specific steam consumption, specific fuel consumption and turbine heat rate (heat rate) will decrease, while the efficiency of the turbine will increase